Chemical Composition and Levels of Heavy Metals in Fish Meat of the Cyprinidae Family from Zhrebchevo Dam, Central Bulgaria - Georgi I. Zhelyazkov (Ecologia Balkanica, 2018)
The aim of the study was to determine the chemical composition and for the first time - the content of cadmium (Cd), nickel (Ni), lead (Pb) and zinc (Zn) in the meat of bream (Abramis brama Linnaeus, 1758), Prussian carp (Carassius gibelio Bloch, 1782), vimba (Vimba vimba Linnaeus, 1758 ) and chub (Leuciscus cephalus Linnaeus, 1758) in one of the most popular for angling dams in Central Bulgaria in order to evaluate the risk for human health. Chemical composition of fish from Zhrebchevo dam showed the highest moisture content in the meat of Prussian carp – 82.13±0.04%, and the lowest in that of vimba – 78.51±0.07%. The amount of protein and lipids was highest in vimba meat 18.41±0.23% and 1.88±0.09%, and lowest in the Prussian carp - 16.49±0.01% and 0.25±0.05%. The content of Cd, Ni and Pb in the meat of vimba was the lowest - 0.033±0.001 mg.kg-1, 0.330±0.001 mg.kg-1 and 0.135±0.001 mg.kg-1 and the highest in bream, 0.045±0.004 mg.kg-1, 0.457±0.018 mg.kg-1 and 0.177±0.013 mg.kg-1 respectively. The highest content of Zn was observed in the Prussian carp - 20.170±0.266 mg.kg-1, and lowest in bream - 15.903±0.593 mg.kg-1. The obtained values for the four studied heavy metals were below the maximum permissible level according to the European legislation.